Special Section on Clinical Supervision: A Reflection - Bernard, Janine M. (Canadian Journal of Counselling and Psychotherapy, 2010)
This special issue about clinical supervision offers an array of contributions with disparate insights into the supervision process. Using a synergy of supervision model, the articles are categorized as addressing the infrastructure required for adequate supervision, the relationship dynamics endemic to supervision, or the process of delivering supervision. Three articles were found to span all three categories, and two focused on one aspect of clinical supervision. Beyond being placed within the synergy model, each article is discussed and future research questions are posed. The special issue reflects the range of topics in the supervision literature at large.